2021
DOI: 10.1016/j.trip.2021.100470
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the COVID-19 pandemic on transportation employment: A comparative analysis

Abstract: The COVID-19 pandemic caused a variety of social, economic, and environmental changes. This paper examines the employment-related impacts of the pandemic on workers in the transportation industry compared to other industries, and within different transportation sectors. We estimated random effects logistic regression models to test the following three hypotheses using the monthly Current Population Survey micro-data. One, the transportation industry experienced a greater incidence of unemployment than other in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 58 publications
1
27
0
1
Order By: Relevance
“…Our research shows a 40.42% decline in road transport in China during COVID-19 lockdown between January 23, 2020, to April 8, 2020, providing empirical evidence to theoretical simulation. Furthermore, our empirical result also consistent with the findings by Mack et al (2021) .…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Our research shows a 40.42% decline in road transport in China during COVID-19 lockdown between January 23, 2020, to April 8, 2020, providing empirical evidence to theoretical simulation. Furthermore, our empirical result also consistent with the findings by Mack et al (2021) .…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
“…Anecdotal evidence reported in medias suggested that transportation industry was hit hard by the pandemic, such as shortage of truck drivers, lack of containers during the pandemic. The latest research found that workers in the transportation sector were 20.6% more likely to be unemployed because of the pandemic than workers in non-transportation industries ( Mack et al, 2021 ). Meanwhile, governments started experimenting with different policies to restore economic activities and supply chain, promoting logistics industry.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of warehousing, the number of goods using warehouse services before the export or import of goods decreases. Another research also figure out that workers in the transportation sector were 20.6 percent more likely to be unemployed because of the pandemic than workers in non-transportation industries [15].…”
Section: Resultsmentioning
confidence: 97%
“…Between March and April 2020, the generalised world-wide lockdown negatively altered the transportation industry, which uses the types mentioned above of energy. The total number of commercial flights collapsed by 73% in the USA, while truck tonnage transportation by 9.18% (Mack et al 2021 ). Private transportation was also significantly reduced, with a decongestion of highway traffic by around 30% in 2020 compared with 2019.…”
Section: Resultsmentioning
confidence: 99%